2020
DOI: 10.1038/s41598-020-67496-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of medical management on growth and weight in individuals with urea cycle disorders

Abstract: Urea Cycle Disorders Consortium (UCDC) * & European registry and network for Intoxication type Metabolic Diseases (E-IMD) * Low protein diet and sodium or glycerol phenylbutyrate, two pillars of recommended long-term therapy of individuals with urea cycle disorders (UCDs), involve the risk of iatrogenic growth failure. Limited evidence-based studies hamper our knowledge on the long-term effects of the proposed medical management in individuals with UCDs. We studied the impact of medical management on growth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Despite not covering 21OHD patients, the introduction of several registry systems for rare congenital diseases has encouraged us. In the EU, some international collaborationbased registry systems for rare congenital diseases, such as the European Registry and Network for Intoxication type Metabolic Diseases (E-IMD) and the European Registry and Network for Homocystinurias and Methylation Defects (E-HOD), have been established [25,[72][73][74][75]. Further, the Japanese Society for Inherited Metabolic Disease has successfully introduced the registry system, "JaSMIn", for patients with inherited metabolic disease (https://www.jasmin-mcbank.com/, visited 23 April 2021).…”
Section: Database Composition and Improvement Of Screening Programmentioning
confidence: 99%
“…Despite not covering 21OHD patients, the introduction of several registry systems for rare congenital diseases has encouraged us. In the EU, some international collaborationbased registry systems for rare congenital diseases, such as the European Registry and Network for Intoxication type Metabolic Diseases (E-IMD) and the European Registry and Network for Homocystinurias and Methylation Defects (E-HOD), have been established [25,[72][73][74][75]. Further, the Japanese Society for Inherited Metabolic Disease has successfully introduced the registry system, "JaSMIn", for patients with inherited metabolic disease (https://www.jasmin-mcbank.com/, visited 23 April 2021).…”
Section: Database Composition and Improvement Of Screening Programmentioning
confidence: 99%
“…However, the results of this study reflect real‐world data on anthropometrics in screened IMD patients followed up in specialized metabolic centers following the latest recommendations. Our findings are pointing at the need for evaluations of bigger single‐disease study cohorts for all screened IMDs as done before in PKU, 4,24,25 GA1 6 and Gal, 7 or other IMDs, as urea cycle disorders 29 …”
Section: Discussionmentioning
confidence: 66%
“…Our findings are pointing at the need for evaluations of bigger single-disease study cohorts for all screened IMDs as done before in PKU, 4,24,25 GA1 6 and Gal, 7 or other IMDs, as urea cycle disorders. 29 Due to the study design, a distinction or proof that the findings on anthropometric parameters in individuals with IMDs identified by NBS are caused by the type of diet, disease-specific factors (e.g., metabolic impairment, neurotoxins), or an amplification of both cannot be given. Here, single-disease analyses in bigger study cohorts are necessary.…”
Section: Shortcomingsmentioning
confidence: 99%
“…Of note, the restriction of protein intake was related to growth impairment in UCD patients because treatment intensification is required in neonatal-onset patients with severe types of UCDs, such as neonatal-onset OTCD and CPS1D [ 34 ]. Posset et al [ 35 ] suggested that growth impairment was determined by disease severity and associated with diminished or borderline plasma BCAA concentrations, regardless of the degree of natural protein intake. Moreover, patients with neonatal-onset UCDs exhibited severe growth impairment over time.…”
Section: Discussionmentioning
confidence: 99%
“…Even patients with late-onset UCDs are likely to present growth impairment over time. However, LT could contribute to catch-up growth [ 35 ]. Unfortunately, our study did not demonstrate an association between the height and plasma BCAA levels of patients with UCDs.…”
Section: Discussionmentioning
confidence: 99%